(untitled) (Annual of the Faculty of Philosophy in Skopje, 2018)
This paper is a brief overview of ancient theoretical views on letters: how the term ‘epistle’ (έπιστολή, epistula) was defined in ancient times, what was discussed in the theory of letters, what recommendations comprised epistolary decorum and what types of letters were defined in ancient handbooks of letter-writing. The purpose of the paper is to reconstruct ancient epistolary theory based on surviving evidence. Direct evidence of this theory are the excursus on letters in the treatise Περὶ ἑρμηνείας by Demetrius, two postclassical handbooks of letter-writing (“Τύποι έπιστολικοί” and “Έπιστολιμαῖοι χα- ρακτῆρες”), a brief tractate on letters written by the sophist Philostratus of Lemnos, one epistle by Gregory of Nazinanzus and the appendix “De epistulis” at the end of the rhetorical handbook by Gaius Julius Victor “Ars rhetorica”. Indirect evidence, on the other hand, of ancient epistolary theory are the not-so-numerous incidental references to letters and letterwriting that are mainly found in Cicero’s correspondence.